Keefektifan Anonymous Reporting sebagai Jalur Pelaporan dalam Penerapan Whistleblowing System - Puspita, Syahrani Wangi; Wahyuningtiyas, Titania Nur; Cahyani, Fella Ardina; Haryani, Feni; Suryatimur, Kartika Pradana (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
Fraud is an act that is against morals and ethics. Corruption is a part of illegal acts that are very detrimental to the economy. However, there are still many acts of corruption that occur with various backgrounds in various fields. Determine the effectiveness of the application of the Whistleblowing System with anonymous reporting become aims from this study, using the accumulated literature review method and descriptive analysis of previous journals. Anonymous reporting that maintains the confidentiality and privacy of the reporter is able to support the effectiveness of the application of the whistleblowing system by increasing the interest and courage of the reporter to report the violations they find and suspect. The results of this study indicate that the effectiveness of the implementation ofÂ  whistleblowingÂ  system with anonymous reporting can reduce the number of corruption and fraud committed in companies and within the government. Supported by previous research, anonymous reporting can provide courage for whistleblowers when disclosing fraud, because feeling safe, feeling protected is the reason for believing that the reporter can become a whistleblower whose identity is well hidden compared to reporting fraud by revealing his identity. The implementation of an increasingly sophisticated whistleblowing system with the help of technology, is able to increase the number of investigations and settlements of fraudulent acts that occur within companies or government agencies.